Spatiotemporal Patterns and Bifurcation Analysis of a Diffusive Predator-Prey Model with Hyperbolic Mortality - Sivakumar, M.; Dharani, S.; Balachandran, K. (Journal of Applied Nonlinear Dynamics, 2026)
The dynamics of the predator-prey system with hyperbolic mortality subject to Neumann boundary conditions are investigated. Stability of the positive equilibrium have been discussed through distribution of the eigenvalues. With different initial values, rich spatial patterns in Turing-Hopf domain are obtained. Especially, the labyrinthine-like patterns are also discovered close to the codimension two Turing-Hopf bifurcation point under suitable conditions.